ANALISIS PENGARUH PENGEMBANGAN KARIR, FASILITAS KERJA DAN STRES KERJA TERHADAP NIAT PINDAH KERJA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA KARYAWAN OUTSOURCING PT PUTRA MANDALA SAKTI - Lutfi‘ Asyarotul Umam (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study aims to analyze the effect of career development, work facilities, and job stress on turnover intention, with job satisfaction as an intervening variable among outsourced employees of PT Putra Mandala Sakti. This research employed a quantitative approach using a survey method by distributing questionnaires to 82 respondents. Data were analyzed using the Partial Least Squares (PLS) technique to examine both direct and indirect relationships among the variables. The results show that: (1) career development does not affect turnover intention; (2) work facilities do not affect turnover intention; (3) job stress has a positive and significant effect on turnover intention; (4) job satisfaction has a negative and significant effect on turnover intention; (5) career development has a positive and significant effect on job satisfaction; (6) work facilities do not affect job satisfaction; and (7) job stress has a negative and significant effect on job satisfaction. The mediation analysis indicates that: (1) job satisfaction serves as an intervening variable in the relationship between career development and turnover intention; (2) job satisfaction does not serve as an intervening variable in the relationship between work facilities and turnover intention; and (3) job satisfaction serves as an intervening variable in the relationship between job stress and turnover intention. The R-square values indicate that career development, work facilities, and job stress explain 53.7% of the variance in turnover intention and 37.7% of the variance in job satisfaction.